Church, Disability, and Rurality: The Lived Experience. (2nd January 2018) - Short, Monica; Seiffert, Murray; Haynes, Rob; Haynes, Leanna
ABSTRACT: The authors document a co-operative inquiry involving two social workers, a sociologist, and a theologian, each with personal and professional connections to disability and rurality. They consider the following research question: How do the inquirers perceive the Anglican Church of Australia located in rural, regional and remote communities engage with people living with disabilities? The authors present from a sociological viewpoint the rural Anglican Church of Australia's influence on personal constructs of disability and how these constructs can lead to either inclusion or rural isolation. It reflects through a social work lens on the church's actions in engaging with, advocating for, and ensuring access to services for people living with disabilities who are located in rural areas. Christian theology can critique and deconstruct discriminatory labels that exclude people living with disabilities within a non-urban community, reclaims the concept of weakness and strength from negative stereotypes, and points people living with disabilities toward the hope found in the resurrection of Jesus Christ. The authors amplify the view that all people are to be included in all aspects of the rural Anglican Church of Australia and in general society.